The Influence of Depression, Anxiety, and Stress on Ageism Among Undergraduates: Mediating Roles of Life Satisfaction, Gratitude, and Prosociality - Chen S; Wan Z (Psychology Research and Behavior Management)
Se Chen,1 Zhonglei Wan2 1School of International Education, Jiangxi Science and Technology Normal University, Nanchang, Jiangxi, People’s Republic of China; 2Department of General Education, Jiangxi Youth Vocational College, Nanchang, Jiangxi, People’s Republic of ChinaCorrespondence: Se Chen, Jiangxi Science and Technology Normal University, 589 Xuefu Avenue, Nanchang, Jiangxi Province, 330038, People’s Republic of China, Tel +0086 – 18679059130, Email chense063@foxmail.comBackground: The rapid growth of the global aging population highlights the need to address ageism and promote social inclusiveness. While considerable research has explored the impact of perceived ageism on older adults’ mental health, limited attention has been given to how negative mental health factors—such as depression, anxiety, and stress (DAS)—influence ageist attitudes among younger populations, along with the psychological mechanisms underlying this relationship.Purpose: This study first investigates the prevalence of ageism among undergraduates and its variation across certain socio-demographic factors at the research site. It then examines the predictive effects of depression, anxiety, and stress (DAS) on ageism, accounting for these socio-demographic factors. Finally, the study explores how DAS influences ageism both directly and indirectly through life satisfaction, gratitude, and prosociality.Design and Settings: A cross-sectional study conducted at 11 higher education institutions in Jiangxi, China.Participants: A total of 1,213 undergraduates participated in the study between July and August 2024. Following data cleaning, 1174 responses were included for analysis.Methods: Data were collected using online questionnaires. T-tests and ANOVA assessed socio-demographic differences in ageism, and regression analysis examined DAS’s predictive effects. Structural Equation Modeling (SEM) explored the pathways linking DAS to ageism via mediators.Results: A moderate level of ageism was observed, with significant variations across socio-demographic factors like academic year, physical health, and contact with older adults. Depression and stress directly predicted ageism, while anxiety had indirect effects via depression and stress. DAS—as a composite construct—indirectly affected ageism via life satisfaction, gratitude, and prosociality.Conclusion: Educational interventions should not only target the reduction of ageist attitudes but also address the underlying mental health conditions that fuel these biases. Promoting life satisfaction, gratitude, and prosociality, along with fostering meaningful intergenerational interactions, will be crucial for developing more effective strategies to combat ageism.Plain Language Summary: Our study investigated how psychological factors like depression, anxiety, and stress (DAS) affect undergraduates’ attitudes toward older adults, particularly ageism—a form of prejudice against older individuals. While previous research has often focused on how ageism negatively impacts older adults’ mental health, few studies have looked at whether the mental health of young people plays a role in shaping these attitudes.To investigate this, we surveyed undergraduate students from 11 higher education institutions in Jiangxi Province, China. We examined how DAS is related to ageist attitudes and whether positive traits, such as life satisfaction, gratitude, and prosociality (the tendency to help others), could lessen the negative influence of DAS on ageism.Our findings show that students with higher levels of depression, anxiety, or stress are more likely to hold negative views about older adults. However, positive traits like gratitude, life satisfaction, and prosociality—as well as meaningful interactions with older adults—appear to soften or reduce the harmful effects of DAS on ageism.These results suggest that improving mental health, fostering positive traits, and facilitating quality interactions between young and older generations could be effective strategies for reducing ageism. This research has important implications for educational programs aimed at promoting respect and empathy across generations.Keywords: mental health, ageism, life satisfaction, gratitude, prosociality, undergraduates